INVESTMENTS IN THE GREEN ECONOMY INITIATIVES AND THEIR INFLUENCE ON THE PROFIT OF ECONOMIC SUBJECTS - Azizakhon F. Gafurova; Umida F. Gafurova; Mokhinur Dilshod qizi Rakhimova; Dilafruz S. Nasirkhodjaeva (International Journal for Quality Research)
This article dwells on the interconnection between the processes of investing in the green economy and the financial results of economic subjects. Attention is paid to theoretical and methodological substantiation of the presence of this connection and the availability of different approaches to the treatment of expenditures for solving environmental problems through financial profit. The formation of a new paradigm, within which investing in green projects is considered a factor of new opportunities, development, and effectiveness, is noted. The essence of the green economy and its components is considered, with an analysis of each component and its contribution to achieving the Sustainable Development Goals and green transition. The mechanism of the influence of environmental investments on the formation of financial results of economic subjects is determined, and the influence of investments by individual components of the green economy in expenses and revenues is identified. The volume and structure of investment expenditures on green economy initiatives are analysed, the need for such investments is established, and the necessity for raising the volume of investments to achieve zero emissions until 2050 is emphasized. Results of correlation analysis are given, which confirm the connection between the level of green economy development and the general level of economic development.